Financial Valuation Workbook Fourth Edition : Step-by-Step Exercises and Tests to Help You Master Financial Valuation. - Hitchner, James R. (John Wiley & Sons, Incorporated, 2017)
This is an all-encompassing valuation handbook that presents the application of financial valuation theory for business appraisers and consultants.